2021
DOI: 10.1061/(asce)st.1943-541x.0003108
|View full text |Cite
|
Sign up to set email alerts
|

Structural Performance of the Esfahan Shah Mosque

Abstract: Structural assessment and seismic vulnerability of ancient masonry buildings is a difficult task even when employing advanced specialized technical skills, which requires a complex study. This paper aims to assess the structural and seismic safety of the Esfahan Shah Mosque in Iran by numerically investigating the nonlinear behavior of the mosque for different scenarios and identify if there is a correlation between crack patterns resulting from numerical analysis, inspection and historical evidence. Firstly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…(3) (4) (5) In the establishment of the frequency-temperature relation, it is evident that the natural frequencies were highly susceptible to change. Besides, identical frequencies with the previous study in 2019 are observed during the continuous monitoring.…”
Section: Continous Monitoring Of the Towermentioning
confidence: 99%
See 1 more Smart Citation
“…(3) (4) (5) In the establishment of the frequency-temperature relation, it is evident that the natural frequencies were highly susceptible to change. Besides, identical frequencies with the previous study in 2019 are observed during the continuous monitoring.…”
Section: Continous Monitoring Of the Towermentioning
confidence: 99%
“…The modal properties were applied in the calibration of the FE model to perform nonlinear analysis and obtain a relation between the simulated damages and the monument. The study suggested improving the stiffening walls and the two domes connection for better global performance [5].…”
Section: Introductionmentioning
confidence: 99%
“…Other scholars have focused on the spatial functionality of mosque architecture [13,14], its refuge capabilities [15,16], seismic resistance [17,18], dome lighting performance [19], and architectural energy efficiency [20]. Research on individual structures mainly focuses on architectural structural performance [21], column styles [22], and visual comfort [23]. Current research is predominantly concentrated in regions with a high Muslim population, such as Saudi Arabia [24], Iran [25], and Algeria [26], in Western Asia and North Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the many methods of structural analysis available [3], numerical methods based on Finite Element Analysis (FEA) have gained popularity in recent years because of increased computation capability that allows for modelling complex geometry using more realistic material models that can simulate the nonlinear behaviour of masonry. There are many examples in the literature that successfully applied this approach in the analysis of heritage sites around the world [4][5][6][7][8][9]. In situ experimental campaigns are complementary and requisite to feed numerical models with real data from the structure and provide the means to calibrate and validate numerical models [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There are many examples in the literature that successfully applied this approach in the analysis of heritage sites around the world [4][5][6][7][8][9]. In situ experimental campaigns are complementary and requisite to feed numerical models with real data from the structure and provide the means to calibrate and validate numerical models [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%